Issues of natural and practical processes modeling to "algebra of vectors" (Journal of Science-Innovative Research in Uzbekistan, 2023)
In this article, problems related to the concept of vector are presented in  various sciences, and the importance of modeling these problems into vector algebra  and different approaches are mentioned